Carrying capacity of Saccharina latissima cultivation in a Dutch coastal bay: a modelling assessment. (24th February 2022) - Jiang, Long; Blommaert, Lander; Jansen, Henrice M; Broch, Ole Jacob; Timmermans, Klaas R; Soetaert, Karline
Abstract: Kelp cultivation receives increasing interest for its high-value products and ecological services, especially in Europe and North America. Before industrial kelp farming in marine ecosystems continue to scale up, evaluation of the site-wide production relative to ecological carrying capacity (CC) of the identified system is essential. For this purpose, a mechanistic kelp model was developed and applied for hypothetical numerical experiments of expanding the farming area in a Dutch coastal bay (the Eastern Scheldt), where cultivation of Saccharina latissima (sugar kelp) is emerging. The kelp model was implemented within a three-dimensional hydrodynamic–biogeochemical model to account for the environmental interactions. The model captured the seasonal growth dynamics of S. latissima, as well as its carbon and nitrogen contents measured at the Eastern Scheldt pilot sites. The model results suggest that expanding the kelp farming area to ∼1–30% of the bay (representing ∼3.4–75 kt harvest dry weight in the 350-km 2 bay) had the potential to weaken the spring bloom, and thereby affected the coexisting shellfish culture in the bay. Competition between S. latissima and phytoplankton mostly occurred in late spring for nutrients (dissolved inorganic nitrogen). The ecological CC should be weighed according to these negative impacts. However, the production CC was not reached even when farming ∼30% of the Eastern Scheldt, i.e. harvesting totally 75 kt dry mass, given that the simulated overall S. latissima production kept increasing with the farming activity. Our modelling approach can be applied to other systems for S. latissima cultivation and assist in assessing CC and environmental impacts.